2019
DOI: 10.4103/jehp.jehp_461_18
|View full text |Cite
|
Sign up to set email alerts
|

A correlational study of hope and its relationship with spiritual health on hemodialysis patients

Abstract: BACKGROUND: One of the main psychological problems in hemodialysis patients is hopelessness. Spiritual health leads the patients toward hope and goal in life. Given the importance of the issue and the little research in this area, this study aimed to assess hope and its relationship with spiritual health on hemodialysis patients in Rasht Razi Hospital of Iran. MATERIALS AND METHODS: This correlational study carried out on 103 patients who admitted in Rasht Razi Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…Tavassoli et al indicated that the mean score of hope was 36.36 in hemodialysis patients. 33 Similarly, Gao et al reported a moderate mean score of hope among hemodialysis patients. 34 However, a study on hope in hemodialysis patients demonstrated that most of the participants (62%) had high levels of hope.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Tavassoli et al indicated that the mean score of hope was 36.36 in hemodialysis patients. 33 Similarly, Gao et al reported a moderate mean score of hope among hemodialysis patients. 34 However, a study on hope in hemodialysis patients demonstrated that most of the participants (62%) had high levels of hope.…”
Section: Discussionmentioning
confidence: 94%
“…Hope therapy reduced depression, anxiety, and stress in hemodialysis patients. 37 Hope was also associated with spiritual well-being, 35 spiritual health, 16,33 and perceived social support 38 in dialysis patients. In fact, hope predicted the quality of life in these patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, it is noteworthy that there was little mention of hope among the participants in this study. Hopes of hemodialysis patients vary according to the age of the study group and study tools, but hopes may be important because they may be related to spiritual health [ 26 , 27 , 28 ]. In this study, the feelings of resentment toward treatment and a longing for a life extended by haemodialysis were opposing experiences that can be distinguished from reconciliation or hope for a new life.…”
Section: Discussionmentioning
confidence: 99%
“…Generally when we are well we run after lots of things being stressed, forgetting about God, about spirituality, about praying (Tavassoli et al, 2019). But when we have to face difficulties, when we have to go through a health problem, those are the moments when we remember that above us is God.…”
Section: Introductionmentioning
confidence: 99%